Delayed facial nerve palsy after surgery for the Esteem® fully implantable middle ear hearing device. (April 2014) - Barbara, Maurizio; Volpini, Luigi; Monini, Simonetta
Abstract Conclusion: Delayed facial nerve (FN) impairment was shown to occur after Esteem® surgery, and taste disturbances were found in a limited number of subjects. Thus, when this type of active middle ear implant (AMEI) is to be implanted, these specific complications need to be shared with the candidate. Objectives: To report on FN involvement in Esteem® AMEI surgery. Methods: A total of 23 males and 11 females, who presented with sensorineural hearing loss of varying severity, underwent surgical implantation of the Esteem® AMEI. FN function was assessed according to the House-Brackmann (HB) grading system. A specific question regarding taste impairment was administered to each patient on the first day and 3 months after surgery. Results: None of the patients presented with a FN deficit in the first postoperative days. In three patients (8.8%), FN palsy developed after 7 days (two patients) and 10 days (one patient), and the severities were HB 4 (two cases) and HB 5 (one case). All patients fully recovered (HB 1) after 6–8 weeks. In 10 of the 34 implanted subjects (29.4%), taste disturbances were found on postoperative day 1, and these impairments remained in only 6 (17.6%) patients at the 3-month postoperative follow-up.